2019
DOI: 10.1002/cav.1899
|View full text |Cite
|
Sign up to set email alerts
|

Investigating cultural aspects in the fundamental diagram using convolutional neural networks and virtual agent simulation

Abstract: This paper presents a study, organized in two phases, regarding group behavior in a controlled experiment focused on differences in an important attribute that vary across cultures—personal spaces. First, we want to study and compare the spatial behavior different populations adopt with respect to their personal space. Second, we want to use simulation of virtual agents to artificially generate movements of people in similar situations and validate them using real video sequences. Our main goal is to be able t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A culture factor is one of the factors that influence the fundamental diagrams (FDs) [ [3] , [4] , [5] ]. However, the study also wants to consider geographical location in this experiment.…”
Section: Location/cultural Differences In Speed–density Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…A culture factor is one of the factors that influence the fundamental diagrams (FDs) [ [3] , [4] , [5] ]. However, the study also wants to consider geographical location in this experiment.…”
Section: Location/cultural Differences In Speed–density Relationmentioning
confidence: 99%
“…Researchers of pedestrian behaviour and crowd modelling have recently taken notice of the importance of studying and modelling social group behaviour [ [1] , [2] , [3] , [4] , [5] ]. It is critical to understand and model groups to recreate crowd behaviour during normal and emergencies since groups make up a significant proportion or even the majority of urban pedestrian crowds [ 6 , 7 ] and exhibit group-specific behaviours [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent work presents approaches in crowd level [11,12,37]. In [11], the authors propose a light-weight and fast fully-convolutional neural network to learn a regression model for crowd counting in images acquired from drones.…”
Section: Previous Approaches In Cultural Behaviorsmentioning
confidence: 99%
“…[12] introduces a crowd detection method for drone safe landing. In the work presented in [37], the authors proposed an approach to detect cultural aspects from crowds using Convolutional Neural Networks (CNN).…”
Section: Previous Approaches In Cultural Behaviorsmentioning
confidence: 99%
“…On this subject, Chattaraj et al [8] suggested that cultural and population differences could produce deviations in speed, density and flow of the crowd. In [29], the authors presents a study regarding group behavior in a controlled experiment focused on differences in an important attribute that vary across cultures -the personal spaces, this study was conducted in two countries: Brazil and Germany. Cultural aspects are specific to a group of individuals.…”
Section: Introductionmentioning
confidence: 99%